Studies on biosurfactant produced using Exiguobacterium profundum - Nur Asni Setiani; Welly Octaviyani; Syarif Hamdani; Irma Mardiah (Indonesian Society for Biochemistry and Molecular Biology, 2019)
Background: The manufacture of pharmaceutical preparations generally adds surfactants. Microbial biosurfactants can be an alternative because biodegradable and have antibacterial properties. Objective: This study aimed to examine the biosurfactant activity of Exiguobacterium profundum. Methods: Hemolysis and spreading oil tests were performed as an initial screening. Biosurfactant production was carried out by growing bacteria on oil-enriched media with shaker system for 7 days. Biosurfactant activity can be seen from the emulsification index, while the characterization of biosurfactant were used thin layer chromatography and antibacterial qualitative testing. Results: Exiguobacterium profundum could spread the oil layer and form micelles. The emulsification index on days 0, 1, 3, 5, and 7 showed percentage in sequence 44.83%, 48.28%, 48.28%, 40%, and 43.75%. The result of TLC showed lipopeptide group which is marked with red stain with ninhydrin appearance. Antibacterial testing using Escherichia coli showed the formation of clear zones around the disk paper. Conclusion: The biosurfactant produced by Exigoubacterium profundum can be classified into lipopeptide group which has antibacterial activity against gram-negative.